An improved approach for analysis of coupled structures in Energy Finite Element Analysis using the coupling loss factor. (November 2018) - Liu, Zhihui; Niu, Junchuan; Gao, Xiang
Highlights: An alternative coupling approach for EFEA based on CLFs is presented. This method is implemented by FEM and the direct wavefield is considered. This method can be used for structures with strong energy-absorbing ability. Abstract: An alternative and improved approach for the analysis of coupled structures in Energy Finite Element Analysis (EFEA) is presented, which is termed as iEFEA in this paper. The conventional EFEA uses the power transfer coefficients (PTCs) to establish the power coupling relation on discontinuous joints, where PTCs are usually derived and processed by the wave transmission approach based on the diffuse wavefield assumption. However, the PTCs in conventional EFEA cannot capture wave filtering effects and only provide accurate predictions when the damping effect is weak. Inspired by the power coupling concept of Statistical Energy Analysis (SEA), an alternative approach using the coupling loss factors (CLFs) and considering the direct wavefield is developed. The present approach is implemented by Finite Element Method (FEM), and thus it inherits the advantages of FEM on handling geometrical complexity and material complexity. The applications of the present approach on coupled beams and coupled plates are demonstrated. The validation simulations show the accuracy and reliability of the present approach.